Size of the Ovulatory Follicle Dictates Spatial Differences in the Oviductal Transcriptome in Cattle. - Angela María Gonella-Diaza; Sónia Cristina da Silva Andrade; Mariana Sponchiado; Guilherme Pugliesi; Fernando Silveira Mesquita; Veerle Van Hoeck; Ricardo de Francisco Strefezzi; Gustavo R Gasparin; Luiz L Coutinho; Mario Binelli (PLoS ONE)
In cattle, molecular control of oviduct receptivity to the embryo is poorly understood. Here, we used a bovine model for receptivity based on size of the pre-ovulatory follicle to compare oviductal global and candidate gene transcript abundance on day 4 of the estrous cycle. Growth of the pre-ovulatory follicle (POF) of Nelore (Bos indicus) cows was manipulated to produce two groups: large POF large corpus luteum (CL) group (LF-LCL; greater receptivity) and small POF-small CL group (SF-SCL). Oviductal samples were collected four days after GnRH-induced ovulation. Ampulla and isthmus transcriptome was obtained by RNA-seq, regional gene expression was assessed by qPCR, and PGR and ERa protein distribution was evaluated by immunohistochemistry. There was a greater abundance of PGR and ERa in the oviduct of LF-LCL animals thus indicating a greater availability of receptors and possibly sex steroids stimulated signaling in both regions. Transcriptomic profiles indicated a series of genes associated with functional characteristics of the oviduct that are regulated by the periovulatory sex steroid milieu and that potentially affect oviductal receptivity and early embryo development. They include tissue morphology changes (extra cellular matrix remodeling), cellular changes (proliferation), and secretion changes (growth factors, ions and metal transporters), and were enriched for the genes with increased expression in the LF-LCL group. In conclusion, differences in the periovulatory sex steroid milieu lead to different oviductal gene expression profiles that could modify the oviductal environment to affect embryo survival and development.